Pengembangan Modul Pembelajaran Fisika Berbasis Model Pembelajaran Guided Discovery Learning Pada Kelas XI IPA SMA Negeri 1 Ulakan Tapakis - finsi, chintia yola; Anaperta, Megasyani; Helendra, Helendra (Universitas Islam Negeri Imam Bonjol Padang, 2021)
The purpose of this study was to see the validity and practicality of the physics learning module based on the Guided Discovery learning model in class XI students of SMA Negeri 1 Ulakan tapakis.This type of research is research and development (R&D). The subjects of this research trial were 32 students of class XI IPA at SMA Negeri 1 Ulakan Tapakis. The data collection instruments used were in the form of expert validation questionnaires and practical test questionnaires for educators and students. The data analysis technique used is the analysis of the validity of the module and the analysis of the practicality of using a physics learning module based on the guided discovery learning model. From the results of the analysis of the learning module validation test, the developed module was categorized as very valid with a validity level of 84,56%. The practicality level of the module from educators and students is 86.03% with a very practical category.Keywords:Â Physics Learning Module, Guided Discovery Learning, Validity.